2008
DOI: 10.1103/physrevlett.101.092701
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Quasifission Modes in theS32+Th232Reaction

Abstract: Comprehensive fission measurements, including mass-angle distributions, for the reaction of 32S with the prolate deformed nucleus 232Th at near-barrier energies show two distinct components in both mass and angle; surprisingly, both have characteristics of quasifission. Their relative probabilities vary rapidly with the ratio of the beam energy to the capture barrier, suggesting a relationship with deformation aligned (sub-barrier), or antialigned (above-barrier), configurations at contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 20 publications
10
107
1
Order By: Relevance
“…This may not be surprising, since nuclear fusion requires the merger of two individual quantum systems, each with their own individual shell structure. In particular, heavy statically deformed nuclei show [4][5][6][7] suppression of fusion when the long axis is aligned with the contact angle of the lighter nucleus (called deformation alignment). This condition applies in collisions at sub-barrier energies.…”
Section: Mass-angle Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may not be surprising, since nuclear fusion requires the merger of two individual quantum systems, each with their own individual shell structure. In particular, heavy statically deformed nuclei show [4][5][6][7] suppression of fusion when the long axis is aligned with the contact angle of the lighter nucleus (called deformation alignment). This condition applies in collisions at sub-barrier energies.…”
Section: Mass-angle Distributionsmentioning
confidence: 99%
“…To define the smooth trends in quasifission, a large number of MAD measurements have been selected from measurements recently made at the ANU [3][4][5][11][12][13][14][15][16][17]. By investigating empirically those nuclear stucture variables that affect quasifission, the ultimate goal to have a reliable predictive model of quasifission, including all relevant physics, will be a step closer.…”
Section: Mass-angle Distributionsmentioning
confidence: 99%
“…Quasifission mass-angle distributions (MAD) first measured at GSI in the 1980s [2,5] showed that quasifission timescales could often be shorter than the rotation time of ∼10 −20 s. However, subsequently only a few measurements [6,7] were made until recent years, when an extensive series of experiments (using the Australian National University Heavy Ion Accelerator Facility and CUBE spectrometer) were carried out [3,[8][9][10][11][12][13][14][15][16]. The kinematic coincidence technique used in the measurements [2,3,17] provides direct information on the mass-ratio of the fragments at scission; thus, the data are represented in terms of mass ratio M R , rather than pre-or According to the characteristics of the MAD (minimum mass yield at symmetry, mass-angle correlation with peak yield at symmetry, and no significant mass-angle correlation), they are assigned as type MAD1, MAD2 and MAD3 respectively [3].…”
Section: Introductionmentioning
confidence: 99%
“…To define the smooth trends in quasifission, a large number of MAD measurements have been selected, for beam energies somewhat above the capture barrier (typically by ∼ 6%). Here the known effects of deformation alignment [10,11,17,19] and shell structure observed in measurements at below-barrier energies [14,20] are much reduced [11,21,22]. However the beam energies should not be too far above the capture barriers, otherwise high angular momenta would be introduced in the collisions, which would then not be representative of heavy element formation reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation